P304 Faecal calprotectin as surrogate marker of transmural healing assessed using MRI in patients with Crohn's disease. (16th January 2018) - Allimant, C; Messadeg, L; Minet Quinard, R; Goutte, M; Bouvier, D; Goutorbe, F; Pereira, B; Bommelaer, G; Hordonneau, C; Buisson, A
Abstract: Background: Mucosal healing (MH) is to date the most validated target in Crohn's disease (CD). However, its use is limited by the low acceptability of repeated endoscopies. In this context, faecal calprotectin (Fcal) is a more convenient tool to monitor MH. Recently, transmural healing assessed using MRI was associated with sustained clinical remission and lower risk of surgery. We aimed to assess the performances of Fcal to assess transmural healing in CD. Methods: We included consecutively and prospectively all CD patients requiring MRI. MRI was performed with injected and diffusion-weighted sequences with no bowel cleansing and no rectal enema. The bowel was divided into five segments to be analysed (ileum, right colon, transverse colon, left/sigmoid colon, and rectum). MRI quantitative parameters such as apparent diffusion coefficient (ADC) or relative contrast enhancement (RCE) were assessed. Clermont score and Magnetic Resonance Index of activity (MaRIA) were also calculated. Transmural healing was defined as previously published (no segmental Clermont score > 8.4 or MaRIA > 7 with no stricture and no fistula). Results: Overall, 118 patients were prospectively included (mean age = 25.9 ± 12.7 years, 53.4% of female, 34.7% of current smokers, 33.9% with perianal lesions and 22.9% with prior intestinal resection. Montreal classification was: L1 = 41.0 %, L2 = 10.3 %, L3 = 48.7 %, B1 = 32.5 %, B2 = 40.1 %, B3 = 27.4 %. The patients were treated with anti-TNF (90.0%), thiopurines (39.0%), methotrexate (8.5%), and/or steroids (17.8%). The median values of CDAI, CRP and Fcal were 170 [82–246], 5.9 mg/l [2.3–20.4], and 598 μg/g [139–1800]. The correlation was moderate between Fcal and total MaRIA or total Clermont score (ϱ = 0.40 for both). The correlation between Fcal and MaRIA or Clermont score, respectively, were ϱ = 0.39 ( p = 0.006) and ϱ = 0.38 ( p = 0.007) in patients with isolated ileal location and ϱ = 0.42 ( p = 0.001) and ϱ = 0.45 ( p < 0.001) for patients with ileocolonic location. The correlation was almost perfect between MaRIA and Clermont score (ϱ = 0.96 ; p < 0.0001). Overall, 25 patients (21.2%) achieved transmural healing. The median value of Fcal was significantly lower in patients with transmural healing (284 μg/g [100–931] vs. 620 μg/g [191–1800], p = 0.023). Using a ROC curve, Fcal < 400 µg/g was the best cut-off value to detect transmural healing (AUC = 0.64; Se = 0.68; Spe = 0.63; PPV = 0.33; NPV = 0.88; accuracy = 0.64). Conclusions: Fcal was moderately correlated with transmural healing in patients with CD. These two tools could be complementary to monitor patients with CD.